Skrining dan Identifikasi Bakteri Laut Penghasil Enzim Selulase yang Berasosiasi dengan Spons - Rika Indri Astuti; Aris Tri Wahyudi; Yohanes Bernadino Putera Saju; Dina Aribah (Institut Pertanian Bogor, 2022)
Marine bacteria associated with sponges can be used as a source of new enzymes, especially cellulase which are potentially used for various industries. The aim of this study was to screen and identify the cellulolytic bacteria associated with sponges. A total of 38 isolates have been successfully isolated from sponges Aaptos sp., Euryspongia sp., and Haliclona sp. by a spread plate method. Amongst 38 isolates, 14 (37%) showed cellulolytic activities in carboxy methyl cellulose (CMC) medium with a cellulolytic index ranging from 0.31 to 1.63. The three highest cellulolytic index was exhibited by bacterial isolates coded Y.5.10, Y.5.11, and Y.40.6. Isolates Y.5.10, Y.5.11, and Y.40.6 showed cellulolytic activity of 0.0053 U/mL; 0.0083 U/mL; and 0.0124 U/mL, respectively, as were tested by spectrophotometry. The highest specific enzymatic activity was showed by isolate Y.40.6 with a value of 0.3391 U/mg. Based on 16S rRNA gene, isolate Y.5.10, Y.5.11, and Y.40.6 were highly similar to (similarity ≥ 99%) Bacillus sp., B. subtilis, and B. cereus, respectively. Keywords: cellulase, isolation, sponge-associated bacteria, 16S rRNA